2022
DOI: 10.3389/fcvm.2022.1057985
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of senescence-related genes in circulating endothelial cells of patients with acute myocardial infarction

Abstract: BackgroundAcute myocardial infarction (AMI) is the main clinical cause of death and cardiovascular disease and thus has high rates of morbidity and mortality. The increase in cardiovascular disease with aging is partly the result of vascular endothelial cell senescence and associated vascular dysfunction. This study was performed to identify potential key cellular senescence-related genes (SRGs) as biomarkers for the diagnosis of AMI using bioinformatics.MethodsUsing the CellAge database, we identified cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…CEBPB plays a critical role in the regulation of immune and in ammatory responses [22]. Several studies have demonstrated that CEBPB is involved in the pathogenesis of myocardial infarction [23]. The present study corroborates the ndings of previous investigations by detecting up-regulation of RAF1 and CEBPB in the context of STEMI.…”
Section: Discussionsupporting
confidence: 91%
“…CEBPB plays a critical role in the regulation of immune and in ammatory responses [22]. Several studies have demonstrated that CEBPB is involved in the pathogenesis of myocardial infarction [23]. The present study corroborates the ndings of previous investigations by detecting up-regulation of RAF1 and CEBPB in the context of STEMI.…”
Section: Discussionsupporting
confidence: 91%
“… 51 A previous bioinformatics analysis study suggests that ZFP36 may be an endothelial cell senescence-related gene in patients with MI. 52 Li et al also found significantly elevated ZFP36 protein levels in ischemic human heart tissue and knockdown of ZFP36 in HCMECs using siRNA significantly inhibited cell proliferation. 53 Our analysis suggests that ZFP36 may be one of the targets of endothelial cell injury by NETs during MI and may be a promising novel target for the treatment of ischemic heart disease.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, our study exclusively assessed gene expression levels during the early stages of AMI, without accounting for temporal changes in gene expression over time. Some genes may show association with prognosis only in the late stage of STEMI, such as aging-related genes ETS2 [ 24 ]. In summary, the phenomenon that MMP9 and GNLY are not significantly associated with AMI prognosis may reflect the complexity and dynamics of STEMI pathogenesis and prognostic determinants.…”
Section: Discussionmentioning
confidence: 99%